Optimizing performance of rechargeable lithium-ion batteries through computer simulations - Miranda, Daniel António da Silva (2017)
There is an increasing need for larger battery autonomy and performance related to rapid technological advances in portable electronic products such as mobile-phones, computers, e-labels, e-packaging and disposable medical testers, among others. The advantages of lithium-ion batteries in comparison to other battery types, such as Ni-Cd ones, are the fact of being lighter and cheaper, showing high energy density (between 100 and 150 Wh kg-1) and a large number of charge/discharge cycles. The key issues for improving lithium-ion battery performance are specific energy, power, safety and reliability. Typically, the performance of a battery is optimized for either power or energy density through the improvement of electrodes and separator materials. Computer simulations of battery performance are important and critical for optimizing materials and geometries. Models have been developed considering the physical-chemical properties of the materials to be used as electrodes and separators, the choice of the most suitable organic solvents for electrolytes, the geometry and dimensions of the components that make up the battery as well as the porosity of the electrodes. The objective of the present work was the optimization of lithium-ion battery performance through computer simulations based on the Doyle/Fuller/Newman model for separators, electrodes (anode and cathode) and full/half-cells in order to understand the main processes that affect battery performance. Thus, along this work, simulations were developed to improve the performance of a lithium-ion batteries. Thus, simulation of the different battery components (separator and electrodes) were developed. The first simulation explores the influence of the geometrical parameters of the separator (porosity, turtuosity and separator thickness) in the performance of the battery. Then, the optimal relationship between active material, binder and conductive additive for lithium-ion battery cathode was studied. Further, a simulation of an interdigitated battery was performed, where the effect of the number, thickness and the length of the digits on the delivered battery capacity was evaluated. Finally, different conventional and unconventional geometries were evaluated taking into account their suitability for different applications without and with consideration of different thermal conditions. The different thermal conditions included isothermal, adiabatic, cold, regular and hot conditions. In relation to the separator, it was observed that its ionic conductivity depends on the value of the Bruggeman coefficient, which is related to the degree of porosity and tortuosity of the membrane. It was determined that the optimal value of the degree of porosity is above 50% and the separator thickness should range between 1 μm and 32 μm for improved battery performance. For the electrodes, it is shown that optimization of the electrode formulation is independent of the active material type but depends on the minimum value of n, defined as the percentage of binder content /percentage of conductive material, depending also on the discharge rate. The influence of different geometries, including conventional, interdigitated, horseshoe, spiral, ring, antenna and gear, in the performance of lithium-ion batteries was analyzed and the delivered capacity depends on geometrical parameters such as the maximum distance that ions move until occurs intercalation process, the distance between the current collectors and the thickness of the separator and the electrodes. For interdigitated structures, the delivered capacity of the battery increases with increasing the number of digits as well as with increasing thickness and length of the digits. Finally, the influence of the thermal behavior on battery performance was evaluated for the aforementioned geometries under different conditions, isothermal, adiabatic, cold, regular and hot conditions. The gear and interdigitated batteries presented the highest delivery capacity at all thermal conditions. In conclusion, in order to improve the performance of lithium ion batteries, it is necessary optimize the geometric parameters of the separator, the percentages of binder, active material and conductive additive in the cathode, as well as the battery geometry (conventional, interdigitated and unconventional geometries) at different thermal conditions.